The Niemytzki plane is $\varkappa$-metrizable - Wojciech Bielas (Institute of Mathematics of the Czech Academy of Science, 2021)
We prove that the Niemytzki plane is $\varkappa$-metrizable and we try to explain the differences between the concepts of a stratifiable space and a $\varkappa$-metrizable space. Also, we give a characterisation of $\varkappa$-metrizable spaces which is modelled on the version described by Chigogidze.